Mediating Health and Risk Information in WhatsApp and its Impact on Risk Perception and Risk Knowledge During COVID-19 Public Health Emergency (International Journal of Advanced Medical Sciences and Technology (IJAMST), 2023)
WhatsApp is India’s most popular social media application and has emerged as a valuable tool for health and risk communication during the COVID-19 public health emergency (PHE). Public health institutions, WHO and Government agencies used WhatsApp Health Alert to distribute verified, accurate and timely information during the COVID-19 pandemic. This study examines the potential of WhatsApp as a primary source of health and risk information and its impact on users’ risk knowledge and risk perception during the COVID-19 pandemic. We conducted a cross-sectional online survey among 453WhatsApp users in Tamil Nadu during the COVID-19 lockdown in May-August 2021. Most of the respondents used WhatsApp as the primary source of COVID-19 information than other media. COVID-19 information in WhatsApp had a positive and significant impact on users’ risk knowledge and risk perception. Regularly receiving and sharing COVID-19 information, subscribing to and participating in COVID-19-related group chats, and regularly updating WhatsApp statuses about COVID-19 were significant influencers of risk knowledge and risk perception. Future PHE response communication must build on these communication opportunities in WhatsApp rather than routed primarily to traditional methods.